Aerodynamic design of a cooled cooling air system for an aero gas turbine - Duncan Walker; Bharat R. Koli; Apostolos Spanelis; Peter Beecroft (2017)
This paper examines the aerodynamic design requirements of a cooled cooling air system for a large, high by-pass ratio, high overall pressure ratio aero-engine. This can be broken into aerodynamic sub-systems each with their own set of requirements and challenges. A low pressure system is required to deliver air bled from the bypass duct to a heat exchanger for use as a heat sink. Similarly, a high pressure system removes a portion of the hot core engine air from a location downstream of the compressor and ducts this to-and-from the HX for cooling. This cooled air must then be returned, across the main gas path, for use in component cooling. The challenge is to design these sub-systems such that satisfactorily perform their own function whilst integrating into the existing engine architecture. This paper presents an overview of a number of studies which use CFD to explore the design space and develop appropriate designs which were subsequently experimentally validated on several isothermal test facilities. Ultimately the feasibility of designing the aerodynamic sub-systems was demonstrated and a future design strategy established.